2018
DOI: 10.3389/fnhum.2018.00068
|View full text |Cite
|
Sign up to set email alerts
|

Corticospinal Excitability Is Modulated as a Function of Postural Perturbation Predictability

Abstract: Recent studies demonstrated that the corticospinal pathway is one of the key nodes for the feedback control of human standing and that the excitability is flexibly changed according to the current state of posture. However, it has been unclear whether this pathway is also involved in a predictive control of human standing. Here, we investigated whether the corticospinal excitability of the soleus (SOL) and tibialis anterior (TA) muscles during standing would be modulated anticipatorily when perturbation was im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…On the contrary, feedback control is characterized by the initiation of sufficient muscle responses after balance loss to compensate an unpredicted postural disturbance during one-legged standing and to avoid falling. In this respect, recent studies (Wälchli et al, 2017 ; Fujio et al, 2018 ) showed that the central nervous system differently prepares postural responses in expected compared to unexpected stance perturbations. For instance, Fujio et al ( 2018 ) examined motor-evoked potential (MEP) induced by transcranial magnetic stimulation during expected (via acoustic signal) and unexpected (no signal) perturbations, while standing on a moveable platform in healthy young adults (mean age: 27 ± 2 years).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, feedback control is characterized by the initiation of sufficient muscle responses after balance loss to compensate an unpredicted postural disturbance during one-legged standing and to avoid falling. In this respect, recent studies (Wälchli et al, 2017 ; Fujio et al, 2018 ) showed that the central nervous system differently prepares postural responses in expected compared to unexpected stance perturbations. For instance, Fujio et al ( 2018 ) examined motor-evoked potential (MEP) induced by transcranial magnetic stimulation during expected (via acoustic signal) and unexpected (no signal) perturbations, while standing on a moveable platform in healthy young adults (mean age: 27 ± 2 years).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, recent studies (Wälchli et al, 2017 ; Fujio et al, 2018 ) showed that the central nervous system differently prepares postural responses in expected compared to unexpected stance perturbations. For instance, Fujio et al ( 2018 ) examined motor-evoked potential (MEP) induced by transcranial magnetic stimulation during expected (via acoustic signal) and unexpected (no signal) perturbations, while standing on a moveable platform in healthy young adults (mean age: 27 ± 2 years). As a result, the MEP for the tibialis anterior muscle was significantly enhanced under expected compared to the unexpected stance perturbation.…”
Section: Discussionmentioning
confidence: 99%
“…We calculated the peak-to-peak amplitude of each MEP within 40 ms after stimulus onset and compared the amplitudes among the five conditions. We set a reference value as deviation above 1.5× the interquartile range (IQR) from the 3rd-quartile and below 1.5× the IQR from the 1st-quartile as an outlier (Fujio et al, 2018). After the outliers were discarded, we compared the averaged MEP amplitude among the five conditions.…”
Section: Methodsmentioning
confidence: 99%
“…We conducted the present study to determine whether the corticospinal excitability in the ankle muscles is specific to the predictions about the magnitude and the direction of perturbations. Our experiments’ results aimed to further the understanding of recent finding that the prediction of future events related to postural stability is a key modulator of corticospinal excitability (Walchli et al, 2017; Fujio et al, 2018).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation